Utilizing Artificial Intelligence to Improve Adaptive Learning - Erwin Dhaniswara; Benny Novico Zani; Muhammad Subhan Iswahyudi; Muhammad Syafral; Didik Cahyono; Zulaekah Zulaekah (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
When open the training or learning window, there are still many training processes that do not use technology. In today's increasingly competitive era, there are still educational institutions that do not use technology in their teaching and learning activities. It is believed that schools are currently taking advantage of new technologies that make the work of teachers or students easier. AI (Artificial Intelligence) technology is developing very quickly from year to year. Its presence with new functions, functions and perspectives increasingly influences many areas of human life, including the field of education. Artificial intelligence is increasingly finding its way into learning activities in schools and universities. Artificial intelligence is an integral part of the development of educational technology. Of course, this had a significant impact on a person's further professional life. The goal of this research is to use artificial intelligence to promote adaptive learning. The method used in this study is a quantitative research method with a survey design. Data for this study were obtained by filling out a questionnaire via the Google Forms link. The results of this study are that the use of artificial intelligence to enhance adaptive learning provides excellent feedback to students. Through artificial intelligence, schools use applications or media that can automate tasks such as giving suggestions, selecting appropriate teaching materials or adapting the curriculum to student needs. The limitation of this research is that the researcher only investigated at the school level. The researcher also hopes that future researchers can take this research to a higher level and he also hopes that in the future there will be other researchers who can advance this research.